PENERAPAN TEKNOLOGI PRODUKSI PADA BAKSO ITIK DAN NUGGET SEBAGAI UPAYA PENINGKATAN PENDAPATAN PETANI Dl SRAGEN - Ratih Dewanti; Yuli Yanti (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2014)
IBM's activities implemented in Nusupan Wetan, Celep, Kedawung, Sragen with partners "Rejeki Agung" Ducks Farmer Group Suhardi and Women's Group Livestock (KWT) lstinah. The purpose of activities is to improve the income and welfare of farmers through the production of duck meatballs and duck nuggets in vacuum packs and upgrade magerial, financial management (accounting) and marketing. The method used is counseling, mentoring, training, making meatballs and duck nuggets vacuum packaging storage and business management training. Event was attended by 30 participants from Rejeki Agung duck farmer group and KWT In this activity, given 2 meat grinder tool, 1 cooler box, 1 vacuum machine, 1 Rinnai gas stove, gas cylinders and equipment cookware for making meatballs and nuggets. Results showed dedication that these activities can increase the productivity and income of farmers from selling meatballs partners and nuggets compared to only sell in the form of ducks culled. Additionally meatballs skills and nuggets are also improved with refined taste and variation, as well as increased sales and bookings. And the ability to implement marketing strategies in accordance with the state and have made a simple bookkeeping.